Nerve growth factor receptors in equine synovial membranes vary with osteoarthritic disease severity. Issue 2 (31st May 2022) - Kendall, Anna; Ekman, Stina; Skiöldebrand, Eva
Abstract: Nerve growth factor (NGF) is a neurotrophin that has been implicated in pain signaling, apoptosis, inflammation and proliferation. The resultant effects depend on interaction with two different receptors; tyrosine kinase A (TrkA) and p75 NTR . NGF increases in synovial fluid from osteoarthritic joints, and monoclonal antibody therapy is trialed to treat osteoarthritis (OA)‐related pain. Investigation of the complex and somewhat contradictory signaling pathways of NGF is conducted in neural research, but has not followed through to orthopaedic studies. The objectives of this study were to compare the expression of NGF receptors and the downstream regulator BAX in synovial membranes from joints in various stages of OA. The horse was used as a model. Synovial membranes were harvested from five healthy horses postmortem and from clinical cases with spontaneous OA undergoing arthroscopic surgery for lameness. Four horses with synovitis without gross cartilage changes, four horses with synovitis and cartilage damage, and four horses with synovitis and intracarpal fractures were included. Samples were investigated by immunohistochemistry and results showed that nuclear staining of TrkA, p75 NTR and BAX increases in OA‐associated synovitis. TrkA expression increased in early disease stages whereas increases in p75 NTR were most prominent in later disease stages with cartilage damage and fibrosis. Clinical significance: Suppression of NGF may result in varied effects depending on different stages of the osteoarthritic disease process.